Analysis of The Processing of Bagea Cake Products (Study Case of Sinar Fajar Small Business) - Andi Rini Wahyuni; Dhian Herdhiansyah; Yusna Indarsyih; Asriani Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to determine the process of processing bagea cake products at Sinar Fajar Small Business in Kendari City. The location of the research was determined purposively. Data collection was carried out by observation and interview methods. The analytical method used is descriptive analysis. The results showed that the process of processing bagea cake products at Sinar Fajar Small Business began with the stages of material preparation, the dough-making process, the dough-forming process, the baking/oven process, the cooling process, and the packaging process. Production activities carried out by Sinar Fajar Small Business in the production process are carried out 14 times a month. The production volume for one production can process as much as 40 kg of sago flour. A single production effort can produce as many as 250 packs of bagea cakes, assuming 100 small mica plastic wraps, 80 medium mica plastic wraps, and 70 large mica plastic wraps.